2021
DOI: 10.3390/ijms22062884
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Epoxide Hydrolase EphD Is Inhibited by Urea and Thiourea Derivatives

Abstract: The genome of the human intracellular pathogen Mycobacterium tuberculosis encodes an unusually large number of epoxide hydrolases, which are thought to be involved in lipid metabolism and detoxification reactions needed to endure the hostile environment of host macrophages. These enzymes therefore represent suitable targets for compounds such as urea derivatives, which are known inhibitors of soluble epoxide hydrolases. In this work, we studied in vitro the effect of the thiourea drug isoxyl on six epoxide hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In addition, epoxide hydrolases, sigma factors, and WhiB proteins are all characterized as additional M.tb detoxifying strategies to withstand adverse conditions (5153). Our findings indicate that during infection E-ALF-exposed M.tb downregulates some epoxide hydrolases genes ( ephA , ephB, and ephC ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, epoxide hydrolases, sigma factors, and WhiB proteins are all characterized as additional M.tb detoxifying strategies to withstand adverse conditions (5153). Our findings indicate that during infection E-ALF-exposed M.tb downregulates some epoxide hydrolases genes ( ephA , ephB, and ephC ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because electron transfer reactions are the main function of NAD (20), we next determined whether the lower intracellular NAD + and NADH levels in the mutant might be due to increased proton conductance and resulting membrane depolarization, as seen with classical uncouplers. We used the fluorescent dye 3,3′-diethyloxacarbocyanine iodide (3) to measure the membrane potential of Mm cells. Δ melH showed no changes in membrane potential compared to WT under the tested carbon source conditions, although, as expected, the membrane uncoupler carbonyl cyanide m -chlorophenyl hydrazone (CCCP) did reduce the membrane potential compared to untreated mycobacteria (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…The Mtb H37Rv strain has at least six potential epoxide hydrolases (EHs), which belong to the virulence, detoxification, and adaptation functional category (3). EHs convert epoxides to trans -dihydrodiols and play a role in detoxification of xenobiotics and biotransformation of endogenous epoxides, and in signaling-molecule regulation (4).…”
mentioning
confidence: 99%
“…Another EH, EphD, is involved in the processing of epoxy mycolates. Overproduction of EphD leads to an accumulation of mycolic acids and a concomitant decrease in epoxy mycolates ( El-Etr et al, 2004 ; Madacki et al, 2021 ). EphG is known to be involved in detoxification following oxidative damage to lipids ( Madacki et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overproduction of EphD leads to an accumulation of mycolic acids and a concomitant decrease in epoxy mycolates ( El-Etr et al, 2004 ; Madacki et al, 2021 ). EphG is known to be involved in detoxification following oxidative damage to lipids ( Madacki et al, 2021 ). Studies conducted with MesT showed it is essential for the optimal growth of Mtb in the presence of styrene oxide ( Chownk et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%